Description of The Learning Process for Number Concepts Through Lesson Study Among Students at Pontianak Public Junior High School No. 1 - Three Bilan Rezkyta Simatupang (Blantika: Multidisciplinary Journal, 2026)
Mathematics learning at the junior high school level requires instructional practices that promote conceptual understanding, active participation, collaboration, and teacher reflection. Lesson Study offers a collaborative professional development approach through the Plan, Do, and See stages to improve the quality of mathematics instruction. This study aimed to describe the learning process of number concepts through Lesson Study among Grade VII students at SMP Negeri 1 Pontianak. A qualitative descriptive approach was employed involving one mathematics teacher, observer teachers, and 32 Grade VII students. Data were collected through observations, semi-structured interviews, documentation, and field notes, and analyzed using data condensation, data display, and conclusion drawing and verification. The findings showed that Lesson Study supported lesson planning, active classroom participation, and reflective teaching practices. During the Do stage, 87.5% of students actively participated in group discussions, 78.1% answered teacher questions, 75.0% presented discussion results, and 90.6% completed the student worksheets. Nevertheless, several students remained passive, some groups were dominated by individual members, and difficulties persisted in solving contextual problems. The See stage enabled teachers and observers to identify these challenges and formulate improvements. In conclusion, Lesson Study fostered more collaborative, student-centered, and reflective mathematics learning while supporting continuous improvement in teaching practices.